(3GdBjGJ GdHjfGJs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3eMeO Hf KGHJ Hf SYjO GdhQjfdGfi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Ef gPG GdcJGH jTJed Ydi YTQI aUhd , GdaUd GdChd OdGdI GddaX s
(3BNQgG (B:s
(3hCeG GdcdGe ai GdebhdGJ abO QCjfGg efbWYkG Yf eOYh Yde GdefWb , adCLd Pdc eG CONdfGg ai Yde (B( (3cPG (B) (3GdeNJUQ , hGddg JYGdi CYde HGdUhGH cedJ hGdMeO ddg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B204s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs